Recent research developments in regeneration of skeletal muscle - Sakuma, K.; Yamaguchi, A. (The Journal of Physical Fitness and Sports Medicine, 2012)
Over the last decade, extensive progress has been made with regard to our understanding of the molecules that regulate skeletal muscle regeneration. Satellite cells are muscle-specific stem cells located under the basal lamina of muscle fibers, which are responsible for muscle regeneration. This precise coordination of complex stem cell responses throughout adult life is regulated by evolutionarily conserved signaling networks that cooperatively direct and control. This process includes the activation, proliferation, and differentiation of stem cells. This highly regulated process of tissue regeneration recapitulates embryonic organogenesis with respect to the involvement of interactive signal transduction networks. Indeed, various modulators such as insulin-like growth factor-I (IGF-I), hepatocyte growth factor (HGF), and leukemia inhibitory factor (LIF) have been shown to stimulate the activation and proliferation of satellite cells. PI3K (phosphatidylinositol 3-kinase)/Akt/mTOR (mammalian target of rapamycin), calcineurin, and serum response factor (SRF) seem to contribute to muscle regeneration by regulating differentiation of satellite cells. In contrast, myostatin inhibits these processes through forkhead box O (FOXO) and/or SMAD 2/3-dependent signaling. In this review, the recent findings for muscle regeneration are described.